The changing face of Qatar - Nature Research (16552612) (2015)
Qatar has unique demographics that sets it apart from other countries in the Gulf Cooperation Council (GCC) and elsewhere in the world, according to research published in the Journal of Local and Global Health Perspectives . Hekmat Alrouh of Weill Cornell Medical College in Qatar (WCMC-Q) and his colleagues used the World Bank Databank to collect key indicators on the GCC countries between 1980 and 2010. This included population size, age distribution, migrant stock, life expectancy, and birth and mortality rates. According to their findings, Qatar's population of 1.87 million represents an 850% increase since 1980, making it the fastest growing population in the GCC countries. By comparison, the population of the United Arab Emirates increased by 780% during the same period, while those of the rest of the GCC countries increased by just two- to threefold. Just 13.4% of Qatar's population is under 15 years of age, compared to 30% of the Saudi population, 16.8% in the UAE, and 26.6% of the world population, but just 1.1% of its population is aged over 65. Combining these figures, Qatar's age dependency ratio — people aged younger than 15 and older than 65 — is just 17%, the lowest in the world. Qatar and Kuwait have one of the world's highest percentage of migrants, who outnumber Qatari nationals by three to one. This is extreme compared to the rest of the world, where 3.1% of the population is classified as migrants. Qatar also was found to have the highest male ratio in the world, with more than three males per female. Life expectancy in the GCC countries has improved significantly in the past three decades, but Qatar's life expectancy of 78 years is the highest of all the GCC countries. Its fertility and birth rates have been steadily declining, however, so it has the lowest birth rate of all the GCC countries, with just 13 births per 1,000 people. Although Qatar has seen a significant improvement in under-five and maternal mortality rates, and lowest rates of communicable disease and all-cause mortality rates, it has an extremely high prevalence of obesity, and this is continuing to increase. “The most concerning trend is the high rate of obesity, which is relevant not only to Qatar but to the region as a whole,” says Alrouh. “The causes for this are not specific to Qatar, but are a result of global factors that will require concerted efforts to tackle them effectively.” “Lifestyle factors [such as] nutrition and exercise are key in determining outcomes such as obesity. Thus, reversing these trends will require efforts to educate the public about the importance of these issues.” Other Information Published in: QScience.com Highlights, Published by Nature Research for Hamad bin Khalifa University Press (HBKU Press) License: http://creativecommons.org/licenses/by/4.0